Acoustic Manipulation of Intraocular Particles - Leshno, Ari; Kenigsberg, Avraham; Peleg-Levy, Heli; Piperno, Silvia; Skaat, Alon; Shpaisman, Hagay (Micromachines (Basel), 2022)
Various conditions cause dispersions of particulate matter to circulate inside the anterior chamber of a human eye. These dispersed particles might reduce visual acuity or promote elevation of intraocular pressure (IOP), causing secondary complications such as particle related glaucoma, which is a major cause of blindness. Medical and surgical treatment options are available to manage these complications, yet preventive measures are not currently available. Conceptually, manipulating these dispersed particles in a way that reduces their negative impact could prevent these complications. However, as the eye is a closed system, manipulating dispersed particles in it is challenging. Standing acoustic waves have been previously shown to be a versatile tool for manipulation of bioparticles from nano-sized extracellular vesicles up to millimeter-sized organisms. Here we introduce for the first time a novel method utilizing standing acoustic waves to noninvasively manipulate intraocular particles inside the anterior chamber. Using a cylindrical acoustic resonator, we show ex vivo manipulation of pigmentary particles inside porcine eyes. We study the effect of wave intensity over time and rule out temperature changes that could damage tissues. Optical coherence tomography and histologic evaluations show no signs of damage or any other side effect that could be attributed to acoustic manipulation. Finally, we lay out a clear pathway to how this technique can be used as a non-invasive tool for preventing secondary glaucoma. This concept has the potential to control and arrange intraocular particles in specific locations without causing any damage to ocular tissue and allow aqueous humor normal outflow which is crucial for maintaining proper IOP levels.